Privacy and Security within Biobanking: The Role of Information Technology. Issue 1 (2016) - Heatherly, Raymond
Abstract : Along with technical issues, biobanking frequently raises important privacy and security issues that must be resolved as biobanks continue to grow in scale and scope. Consent mechanisms currently in use range from fine-grained to very broad, and in some cases participants are offered very few privacy protections. However, developments in information technology are bringing improvements. New programs and systems are being developed to allow researchers to conduct analyses without distributing the data itself offsite, either by allowing the investigator to communicate with a central computer, or by having each site participate in meta-analysis that results in a shared statistic or final significance result. The implementation of security protocols into the research biobanking setting requires three key elements: authentication, authorization, and auditing. Authentication is the process of making sure individuals are who they claim to be, frequently through the use of a password, a key fob, or a physical (i.e., retinal or fingerprint) scan. Authorization involves ensuring that every individual who attempts an action has permission to do that action. Finally, auditing allows for actions to be logged so that inappropriate or unethical actions can later be traced back to their source.